How foreign direct investment and economic growth affect renewable energy consumption globally: insights from dynamic panel estimators - Tuan Van Tran; Hoi Vu Le; Trang Ngoc Doan Tran; Khoa Dang Duong (Social Sciences and Humanities Open, 2025)
This study investigates the global impact of foreign direct investment and economic growth on renewable energy consumption. We use the Dynamic System Generalized Method of Moments to examine data from 110 countries from 1990 to 2020. Our findings report a U-shaped relationship between Foreign Direct Investment and renewable energy consumption globally. Moreover, the findings indicate that the interaction between Foreign Direct Investment and economic growth affects renewable energy consumption. While these findings align with the trade-off theory and race-to-the-bottom hypothesis, they do not support the conservation Hypothesis. Finally, the findings are helpful for policymakers to design policies that motivate renewable energy consumption globally.